Coupling antitoxins and blue/white screening with parAB/resolvase mutation as a strategy for Salmonella spp. plasmid curing - Dereje D. Gudeta; Shaohua Zhao; Nesreen Aljahdali; Steven L. Foley (Microbiology Spectrum)
ABSTRACT Despite the dissemination of multidrug resistance plasmids, including those carrying virulence genes in Salmonella spp., efficient plasmid curing tools are lacking. Plasmid partitioning and multimer resolution systems are attractive targets for plasmid cure. However, plasmid curing strategies targeting these systems are often hindered by the host addiction system through a process known as post-segregation killing. Here, we developed vector tools that can mutate the above systems while replenishing short-lived antitoxins. Cloning was performed using Gibson assembly. parAB or resolvase (res) genes on Incompatibility Group (Inc)FIB, IncA/C, IncX4, and plasmids carried by Salmonella species were deleted by first knocking in the N-terminal ß-galactosidase encoding gene (bgaB), followed by in-frame insertion of its C-terminal region using pDG1 and pDG2 vectors, respectively. pDG1 was used as a backbone to develop a vector, designated as pDG-At, expressing 13 antitoxins driven by strong promoters. Plasmid curing was achieved by transforming pDG-At to parAB or res mutants followed by blue-white screening and PCR; however, parAB mutant isolation with this method was low and often non-reproducible. To elucidate whether the prior presence of pDG-At in cells improves viable mutant isolation, we re-constructed pDG-At, designated as pDG-Atπ, using a vector with the R6Kϒ origin of replication with its π-factor required for replication under araBAD promoter. Results showed that pDG-Atπ can replicate in the absence of arabinose but can be cured by growing cells in glucose-rich media. Next, we repeated IncFIB’s parAB deletion using pDG1 but in cells carrying pDG-Atπ. Many white colonies were detected on X-Gal-supplemented media but none of them carried the target parA mutation; however, ~80% of the white colonies lost IncFIB plasmid, while the others retained the wild-type plasmid. Similar results were obtained for IncX4 plasmid curing but also found that this method was not reproducible as the white colonies obtained after allelic replacement did not always result in plasmid curing or mutant isolation. This is the first report describing a simple blue/white screening method for plasmid curing that can avoid laborious screening procedures.IMPORTANCEPlasmids play an important role in bacterial physiology, adaptation, evolution, virulence, and antibiotic resistance. An in-depth study of these roles partly depends on the generation of plasmid-free cells. This study shows that vector tools that target genes required for plasmid stability in the presence of an antitoxin-expressing helper plasmid are a viable approach to cure specific plasmids. Expression of bgaB from target plasmids can greatly facilitate visual detection of plasmid cured colonies avoiding time-consuming screening procedures. This approach can be refined for the development of a universal plasmid curing system that can be used to generate plasmid-free cells in other human bacterial pathogens including Gram positives and Gram negatives.